The Effect of Nozzle Temperature, Infill Geometry, Layer Height and Fan Speed on Roughness Surface in PETG Filament - Taqdissillah, Doohan; Muttaqin, Aris Zainul; Darsin, Mahros; Dwilaksana, Dedi; Ilminnafik, Nasrul (Universitas Negeri Malang, 2022)
3D printing is a process of making three-dimensional solid objects from a digital file process created by laying down successive layers of material until the object is created. Many filaments can be used in 3D printing, one of which is PETG (PolyEthylene Terephthalate Glycol). PETG is a modification of PET (PolyEthylene Terephthalate) with added glycol at a molecular level to offer different chemical properties that provide significant chemical resistance, durability, and excellent formability for manufacturing. This study aims to find the most optimal parameter of surface roughness of PETG with different parameters of nozzle temperature, infill geometry, layer height and fan speed. Taguchi L16 (44), with four levels for each parameter, was used to determine the effect of each parameter. Each experiment was repeated five times to minimize the occurrence of errors. Based on the result, the effect of each parameter is nozzle temperature at 4.9%, infill geometry at 5.9%, layer height at 82.3%, and fan speed at 4.6%. Layer height has the highest effect on surface roughness, and other parameters have a low effect, under 7%. Research shows that the optimal combination of parameters is a nozzle temperature of 220 °C, infill geometry zig-zag, layer height of 0.12 mm, and a fan speed of 80 %.